Law No. 11 of the Year 2022 Amending Some Provisions of Law No. 102 of the Year 1986 on the Establishment of New and Renewable Energy Authority and Law No. 203 of the Year 2014 on Stimulating the Production of Electricity from Renewable Energy Sources and Abolishing the Hydro Power Plant Executive Authority Established by Law No. 14 of the Year 1976 on the Establishment of Qattara Depression Project Execution Authority = قانون رقم 11 لسنة 2022 بتعديل بعض أحكام القانونين رقمى 102 لسنة 1986 بإنشاء هيئة تنمية واستخدام الطاقة الجديدة والمتجددة و 203 لسنة 2014 بشأن تحفيز إنتاج الكهرباء من مصادر الطاقة المتجددة وبإلغاء هيئة تنفيذ مشروعات المحطات المائية لتوليد الكهرباء المنشأة بالقانون رقم 14 لسنة 1976 بشأن إنشاء هيئة تنفيذ مشروع منخفض القطارة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic